Learning Mathematics with Contextual Approach to Improve Outcomes Learning Maths in Vocational High School - Masruroh, Ani Ainun; Oktaviani, Rani; Kulsum, Sri Islami; Afrilianto, M. (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
This research aims to improve student learning outcomes on mathematics learning by using a contextual approach. This research is a Class Action Research (CAR) conducted at one of the vocational schools (SMK) in X-class areas of focus on Automation of Governance and Office 3. The research instruments used in this study are (1) tests consisting of pre-test and post-test of the concept of Sigma notation and infinite series; and (2) the use of an observation sheet for teachers and students as a condition of measuring action execution. The procedure of the study consists of (1) planning, (2) The implementation of Action, (3) observation, (4) evaluation, and (5) reflection. The test results showed that there was an increase in pre-test and post-test results of 19.33%. Obviously, this shows that students ' learning outcomes on math learning are increasing after learning using a contextual approach.